Outsourcing Methods for Optimizing the Staff Management of the Economical Organizations - Kireeva-Karimova, A.M.; Hai, Anh. Nguyen; Nuriyahmetova, S.M. (International Journal of Criminology and Sociology, 2022)
The main aim of the study is to investigate the components of the concept of outsourcing, the genesis of its development, analyzes the transformation of outsourcing of information technology systems, defined the place of outsourcing in the practice of Russian and international business. It has given an assessment for the problems of implementation, outsourcing under conditions of uncertainty, types and tools of outsourcing are analyzed, aspects of optimizing the control of production costs at the core of the business, core competencies, non-core assets and types of economical business organizations are analyzed, the problem of overcoming staff resistance to changes during the implementation of the outsourcing program is analyzed, and prospects for implementation of HR-outsourcing are identified.